CONCEPTUAL PRINCIPLES OF PSYCHOLOGICAL SUPPORT OF DIFFERENT STAGES OF THE PROFESSIONAL GENESIS OF LAW ENFORCEMENT OFFICERS - N. E. Miloradova (Law and Safety, 2018)
The objective, tasks and essence of psychological support to the professional genesis of law enforcement officers have been considered. It has been noted that the result of psychological support is the full realization of the psychological potential of the personality of law enforcement officers, the formation of psychological competence in choosing and overcoming the difficulties of personal and professional life.The scientific and practical propositions for the implementation of measures within the framework of diagnostic, preventive and correctional directions of psychological support of pre-university, university and post-university stages of professional development of law enforcement officers have been provided.The author has analyzed the main problem issues of each of the stages:– pre-university (training of specialists for conducting vocational guidance work; involving parents of future cadets in carrying out appropriate selection of professional paths by young men; conducting psychoprophylaxis and psycho-corrective work with children of privileged contingent; features of the crisis of educational and vocational professional orientation; improving the profile pre-university training and professional selection to higher educational institutions of the Ministry of Internal Affairs of Ukraine, etc.);– university (peculiarities of adaptation processes; peculiarities of the revision crisis and the correction of professional selection; integrated approach to optimizing the conditions for prevention of professional crises; training of cadets for the development of a new social role, etc.);– post-university (study of the adaptation characteristics of a young specialist; development of skills of professional time management at the stage of mastering professional activity; peculiarities of the process of overcoming the negative consequences of professionogenetic crises: the crisis of professional growth; the crisis of professional career; the crisis of social and professional self-actualization at the master stage; the crisis of loss and termination of professional activity, etc.).